Pelatihan penanganan nyeri serta mual muntah pada masyarakat penderita gastritis - Feri, Jhon; Juartika, Wella (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Gastritis is one of the most common digestive disorders in the community, often accompanied by symptoms of epigastric pain as well as nausea and vomiting that interfere with the patient's quality of life. Optimal symptom management requires understanding the causative factors and appropriate intervention techniques, both pharmacological and non-pharmacological techniques. This training aims to improve the knowledge and skills of the community in dealing with pain symptoms as well as nausea and vomiting in people with gastritis. The training method includes delivering material through interactive lectures, group discussions, and hands-on practice of non-pharmacological techniques such as diet management, relaxation techniques, and acupressure. In addition, participants were given education about the proper use of drugs according to medical recommendations. The training results are expected to increase public understanding of the importance of early detection, prevention, and treatment of gastritis, as well as reduce dependence on inappropriate treatment. This training is the first step in building a society that cares more about digestive health, with the hope of positively impacting the quality of life of individuals with gastritis and their families.